Analisis Kelimpahan Bakteri Patogen pada Saluran Pencernaan Ikan Sidat (Anguilla bicolor bicolor) Fase Elver dan Fingerling - Nurul Faridah; Muhammad Rizki Fauzi; Angela Mary Gratia Arshania (AGROMAKNA: Jurnal Pertanian dan Peternakan, 2026)
Eels are catadromous fish species that undergo four life phases, namely Leptocephalus, Glass eels, Elvers and Fingerlings in freshwater and marine environments. Eel is an export commodity that is widely cultivated. However, the problem of eel cultivation arises in the form of diseases caused by pathogenic bacteria, especially those that attack the digestive tract. There have not been many studies on the abundance of pathogenic bacteria in the digestive tract of eel, so this study aimed to analyze the abundance of pathogenic bacteria in the digestive tract of eel (Anguilla bicolor bicolor) in the Elver phase (wild and cultivated) and Fingerling. The method used in this study is a literature study using secondary data in the form of identification of pathogenic bacteria and data on the abundance of pathogenic bacteria in the life phase of eel obtained from the research of Kusumawaty et al (2020). All data obtained were analyzed descriptively. The results of the study found that the highest abundance of pathogenic bacteria found in the digestive tract in the Elver and Fingerling phases came from the genera Aeromonas, Pseudomonas, Streptococcus and Vibrio, respectively, while the species found were Aeromonas caviae, Pseudomonas aeruginosa and Streptococcus agalactiae. The highest abundance of pathogenic bacteria was in the Elver phase (Elver wild and Elver cultivated) while the lowest abundance was in the Fingerling phase. The difference in aquatic environmental conditions in the two phases is a factor causing the difference in the abundance of pathogenic bacteria in the digestive tract of the Anguilla bicolor bicolor, mainly because the immune system and digestive system of the Elver have not yet developed, so they are susceptible to disease